2020
DOI: 10.3390/plants9101367
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Maize and Teosinte microRNAs under Submergence, Drought, and Alternated Stress

Abstract: Submergence and drought stresses are the main constraints to crop production worldwide. MicroRNAs (miRNAs) are known to play a major role in plant response to various stresses. In this study, we analyzed the expression of maize and teosinte miRNAs by high-throughput sequencing of small RNA libraries in maize and its ancestor teosinte (Zea mays ssp. parviglumis), under submergence, drought, and alternated stress. We found that the expression patterns of 67 miRNA sequences representing 23 miRNA families in maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…MicroRNAs regulate gene expression by up- or downregulating target genes. Numerous studies have revealed the expression patterns of miRNAs and their target genes under plant drought stress through high-throughput sequencing [ 52 , 62 ]. Herein, a large data set of miRNAs was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs regulate gene expression by up- or downregulating target genes. Numerous studies have revealed the expression patterns of miRNAs and their target genes under plant drought stress through high-throughput sequencing [ 52 , 62 ]. Herein, a large data set of miRNAs was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a microarray expression analysis of a drought-associated study revealed 13 miRNAs families regulating 42 novel mRNAs target and 65 in maize (Li et al, 2020). Another study showed that 23 drought-responsive cis-regulatory elements and three TFs (GAMYB, HD-Zip III, and NAC) were associated with the target mRNAs (Aravind et al, 2017;Sepúlveda-García et al, 2020). The knock-down maize mutants of miR166 showed its association with adaptation through various phenotypic variations.…”
Section: Role Of Micro Rnas In Abiotic Stress Tolerance In Maizementioning
confidence: 99%
“…Importantly, chronological order of stresses largely influenced corresponding plant responses, for example, wild maize (teosinte) plants first treated with drought and then exposed to flooding behaved like flooded‐only plants. The opposite stress order attenuated the drought response, most likely due to the harmful effect of reoxygenation on plant survival (Sepúlveda‐García et al., 2020). Flood‐tolerant willows or adult Chloris gayana , a forage crop grass, acted oppositely and showed little physiological change under flooding stress independent of previous stresses, while staying susceptible to drought stress (Doffo et al., 2017; Mollard et al., 2022).…”
Section: Flooding Stress In Combination With Other Stressesmentioning
confidence: 99%